L’audit Social Comme Outil D’aide A La Gestion Des Ressources Humaines Des Organisations. Cas D’une Organisation Publique Et Une Autre Privée - Rachid Zammar; Noureddine Abdelbaki (European Scientific Journal, ESJ, 2017)
In a context marked by the increasing demands of all stakeholders for human resources policies and practices, expectations of social audit are increasing. The objective of this research is to identify the scope of social audit and to show that it is a tool to assist human resources departments. It tries to address the question of how social auditing can help to anchor appropriate human resource management in an organization's practices. To do this, a field survey was conducted among the staff of two organizations : one public (the urban district of Agadir) and the other private (Medium and Large ATLAS company) via semi-structured interviews. The survey found that the introduction of social auditing in organizations is necessary since the latter has a beneficial effect on human resources management insofar as it ensures a positive social climate.